2018
DOI: 10.2147/bctt.s185960
|View full text |Cite
|
Sign up to set email alerts
|

LXR/RXR pathway signaling associated with triple-negative breast cancer in African American women

Abstract: BackgroundTriple-negative breast cancer (TNBC) is more prevalent in African and African American (AA) women compared to European American (EA) women. African and AA women diagnosed with TNBC experience high frequencies of metastases and less favorable outcomes. Emerging evidence indicates that this disparity may in fact be the result of the uniquely aggressive biology of African and AA disease.PurposeTo understand the reasons for TNBC in AA aggressive biology, we designed the present study to examine the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The combined down-regulation of the LXR/RXR pathway and acute phase response signalling pathway was widely observed in proteomic studies for various cancer types, e.g. for colon adenocarcinomas, 51 for triple-negative breast cancer (in combination with a downregulation of the FXR/RXR activation pathway, 52 which was also found here) and in the urine of prostate cancer patients. 53 LXR acts as sensor for cholesterol homeostasis and in normal cells the pathway is activated by high intracellular cholesterol concentrations to reduce synthesis and influx and enhance cholesterol efflux.…”
Section: Increased Depth Of Analysis Revealed Deep Insights Into the supporting
confidence: 76%
“…The combined down-regulation of the LXR/RXR pathway and acute phase response signalling pathway was widely observed in proteomic studies for various cancer types, e.g. for colon adenocarcinomas, 51 for triple-negative breast cancer (in combination with a downregulation of the FXR/RXR activation pathway, 52 which was also found here) and in the urine of prostate cancer patients. 53 LXR acts as sensor for cholesterol homeostasis and in normal cells the pathway is activated by high intracellular cholesterol concentrations to reduce synthesis and influx and enhance cholesterol efflux.…”
Section: Increased Depth Of Analysis Revealed Deep Insights Into the supporting
confidence: 76%
“…They demonstrated that representations of LXR/RXR signaling pathways were increased in LA samples from AA women and that this pathway was altered in TNBC samples from AA women. Furthermore, they showed that Cyp7B1, the enzyme responsible for the degradation of 27OHC, had strong immunoreactivity in the tumor cells of LA patients and less in TNBC tissues [64].…”
Section: Ohc Oxysterols Lxrs and Breast Cancermentioning
confidence: 99%
“…In particular pharmacological targeting of LXR-ligand production effectively overcome immunotherapy resistance in preclinical melanoma models 16,21 . LXR has also been cited as a marker for poor prognosis, particularly in African American TNBC patients 22,23 . In breast cancer overall, elevated lipid metabolism is irrevocably linked to poor clinical outcomes and treatment resistance 2426 .…”
Section: Introductionmentioning
confidence: 99%